Analytical assessment of the behaviour of extended end plate connection - Nur Fatin Zulaikha, Halijan (2014)
Steel frame structure with beams and columns was become I conventional building structure in construction world. In this study, one out of eight specimens from previous experimental which is specimen FS1a was modelled and simulated using Finite Element Method (FEM) which is ABAQUS/CAE Version 6.10 under static loading. The specimen was model to determine the failure mode at the end plate besides to understand the behaviour of the extended endplate connection. This study was conducted to minimize the cost and time spends for the experiment. The failure modes involved in this analytical model was the weld failure of the assembly beam-end plate which is classified as Mode 1 failure that yielding of the end plate. As a result, moment rotation (M- 4) curve was obtained for analytical model in order to determine the capacity and behaviour of the extended end plate in terms of the resistance, stiffness and rotational capacity. The experimental results were used as a basis of comparison with the analytical results given by the component method of Eurocode 3 EN 1993-1-8. A good agreement was noticed between the analytical values and experimental values. Based on the results obtained, it can be concluded that in terms of rigidity, the classification boundaries of beam-to-column connection was rigid connection and the. extended end plate connection was designed as partial strength Comparisons of connection rotation capacity with the equivalent method in EurOcode 3 EN 1993-1-8 show that the end plate has an adequate rotation capacity for plastic analysis.